ASSESSING THE IMPACT OF THE FLOATING EXCHANGE RATE REGIME: DYNAMICS BETWEEN EXCHANGE RATES AND STOCK PRICES IN THE EGYPTIAN MARKET - Mahmoud Elsayed Mahmoud; Doddy Setiawan; Yanni Aryani (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The study aims to measure the effect of liberalizing the exchange rate and the transition from the fixed exchange rate to the flexible exchange rate on both the exchange rate stock prices and to measure the correlation between both the exchange rate and stock prices on the Egyptian stock, exchange before and after Floating of the exchange rate during the period 2019 and 2023, the variable under the study represent the exchange rate of the Egyptian pound against the us dollar and the EGX30 before and after the Floating of the exchange rate , 2 independent sample both the Mann Whitney test and the spearman’s correlation coefficient were used before and the after Floating of the exchange rate. The analysis revealed a significant impact on both the exchange rate and stock prices subsequent to the floatation of the exchange rate. Additionally, noteworthy significant correlations were observed between the exchange rate and stock prices, both pre and post the exchange rate floatation. These findings emphasize the influential relationship between the exchange rate and stock prices, indicating a notable effect of the exchange rate changes on the stock market dynamics both before and after the exchange rate was floated.